TN

( x + 9 ) + ( x - 8 ) + ( x + 7 ) + ( x - 6 ) + ( x + 5 ) + ( x - 4 ) = 63,6

Help me!

DA
9 tháng 5 2018 lúc 21:32

(x+9)+(x-8)+(x+7)+(x-6)+(x+5)+(x-4)=63,6

x+9+x-8+x+7+x-6+x+5+x-4              =63,6

(x+x+x+x+x+x)+(9-8+7-6+5-4)         =63,6

6x+3                                                 =63,6

6x                                                     =63,6-3

6x                                                     =60.6

x                                                       =60,6/6

x                                                       =10.1

Bình luận (0)
MF
9 tháng 5 2018 lúc 21:29

x + 9 + x - 8 + x + 7 + x - 6 + x + 5 + x - 4 = 63,6

6x+3=63,6

6x=60,3

x=10,05

Vậy x=10,05

Chúc bạn học tốt+-*/

Bình luận (0)
SM
9 tháng 5 2018 lúc 21:43

=> 6x + 3 = 63,6

=> 6x = 60,6

=> x = 10,1

Vậy x = 10,1

Bình luận (0)